What Role Does Body Image in Relationship between Level of Health Literacy and Symptoms of Eating Disorders in Adolescents? - Boberová, Zuzana (Int J Environ Res Public Health, 2021)
(1) Background: The aim of this study was to explore the associations between health literacy and symptoms for eating disorders among adolescents, taking into consideration age and gender and whether this association is mediated by body image. (2) Methods: We used data on 5054 adolescents (mean age = 13.9, 51.7% boys) from the Health Behaviour in School-Aged Children study conducted in 2018 in Slovakia. We used logistic regression models to examine associations between level of health literacy and symptoms for eating disorders mediated by body image. (3) Results: Adolescents with low and medium levels of health literacy had a higher occurrence of reporting two or more symptoms of eating disorders (odds ratio (OR)/95% CI: 2.25/1.78–2.84 and 1.37/1.15–1.65). Adjustment for body image reduced the significance of association between low level of health literacy and symptoms for eating disorders by 26.4%, and association between medium level of health literacy and symptoms for eating disorders by 29.7%. (4) Conclusions: Adolescents who have a low health literacy level were found to have a higher probability of having symptoms for eating disorders, especially when they perceive themselves as fat. The study refers to potential theoretical frameworks for health literacy intervention that may provide guidelines for the intervention design and materials.